Homocysteine is Linked to Macular Edema in Type 2 Diabetes. (July 2014) - Li, Jianbo; Zhang, Hongman; Shi, Min; Yan, Lingfei; Xie, Min
Abstract Aim: To explore the relationship between plasma total homocysteine concentration and diabetic macular edema in patients with type 2 diabetes. Methods: Patients with type 2 diabetes (n = 176) were enrolled in a cross-sectional hospital-based study. Diabetic macular edema status was documented by fundus photographs. Plasma total homocysteine concentration was measured using fluorescence polarization immunoassay. Normal control plasma homocysteine was established in 115 healthy subjects. Risk factors for diabetic macular edema were obtained from fasting blood samples and interviewer questionnaire. Results: Diabetic patients had increased plasma homocysteine compared with normal control. Plasma homocysteine levels were higher in subjects with diabetic macular edema than without ((11.4 ± 2.7) versus (8.5 ± 1.9) (μmol/l), p = 0.000). The association of homocysteine with diabetic macular edema was independent of major risk factors for diabetic macular edema (duration of diabetes, HbA1c, lipid) and determinants of higher homocysteine concentration (age, gender, serum folate and vitamin B12, renal status, and biguanide use) (OR: 1.63 (1.02–2.14), p = 0.018). Furthermore, per increase of 5.0 μmol/l plasma homocysteine was related to macular edema, after controlling for per unit increase of other factors (OR: 1.64 (1.04–2.16), p = 0.019). Conclusions: Plasma total homocysteine concentration is independently associated with the occurrence of macular edema in type 2 diabetes. Future prospective studies are warranted to clarify the relationship.